2007
DOI: 10.1523/jneurosci.4627-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Category Tuning Revealed by Intracranial Electroencephalograms in High-Order Human Visual Areas

Abstract: The functional organization of human sensory cortex was studied by comparing intracranial EEG (iEEG) recordings of local field potentials in neurosurgical patients with functional magnetic resonance imaging (fMRI) obtained in healthy subjects. Using naturalistic movie stimuli, we found a tight correlation between these two measures throughout the human sensory cortex. Importantly, the correlation between the iEEG and fMRI signals was site-specific, exhibiting neuroanatomically specific coupling. In several cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 44 publications
7
72
0
Order By: Relevance
“…Previous studies using invasive recordings have demonstrated that the BOLD signal correlates positively with the signal power of highfrequency local field potentials (LFPs) measured from both auditory cortex (Mukamel et al, 2005;Nir et al, 2007) and visual cortex (Privman et al, 2007) during movie viewing. In addition, the signal power of low-frequency LFPs correlated negatively with BOLD signal (Mukamel et al, 2005).…”
Section: Neurophysiological Differences Between Meg and Fmrimentioning
confidence: 99%
“…Previous studies using invasive recordings have demonstrated that the BOLD signal correlates positively with the signal power of highfrequency local field potentials (LFPs) measured from both auditory cortex (Mukamel et al, 2005;Nir et al, 2007) and visual cortex (Privman et al, 2007) during movie viewing. In addition, the signal power of low-frequency LFPs correlated negatively with BOLD signal (Mukamel et al, 2005).…”
Section: Neurophysiological Differences Between Meg and Fmrimentioning
confidence: 99%
“…2, Privman et al, 2007) in which images from four categories were presented pseudo randomly at a rate of one image per second -each presented for 250 ms and followed by a gray screen for an interval of 750 ms. The patients were requested to press a computer mouse button whenever two consecutive pictures were identical and to refrain from pressing in any other case.…”
Section: Stimuli and Taskmentioning
confidence: 99%
“…1 using a particularly large set of intracranial ECoG recordings encompassing thousands of contacts. Such approach offers both high temporal resolution, good cortical localization (Privman et al, 2007) and extensive coverage of cortical areas. Our study consisted of a large cohort of patients (43) all of which performed The models are presented in the framework of three peaks of activations: an early ($100 ms post stimulus presentation) peak localized to early visual areas (EVA), an intermediate peak ($200 ms) localized to high order visual areas (HVA) and finally a late peak ($300 ms) localized to the global work space at the fronto-parietal cortex (GWS).…”
Section: Introductionmentioning
confidence: 99%
“…Following Mukamel et al (2005), Sawamura et al (2006), andPrivman et al (2007), we estimated the BOLD response by convolving the population response in the size task (Fig. 3) with a standard canonical hemodynamic response function (Boynton et al, 1996).…”
Section: Simulating Bold Responsementioning
confidence: 99%